Too Late! Influence of Temporal Delay on the Neural Processing of One’s Own Incidental and Intentional Action-Induced Sounds - Heins, Nina; Trempler, Ima; Zentgraf, Karen; Raab, Markus; Schubotz, Ricarda I. (Frontiers in Neuroscience, 2020)
The influence of delayed auditory feedback on action evaluation and execution of real-life action-induced sounds apart from language and music is still poorly understood. Here, we examined how a temporal delay impacted the behavioral evaluation and neural representation of hurdling and tap-dancing actions in an functional Magnetic Resonance Imaging (fMRI) experiment, postulating that effects of delay diverge between the two, as we create action-induced sounds intentionally in tap dancing, but incidentally in hurdling. Based on previous findings, we expected that conditions differ regarding the engagement of the supplementary motor area (SMA), posterior superior temporal gyrus (pSTG), and primary auditory cortex (A1). Participants were videotaped during a nine-week training of hurdling and tap dancing; in the fMRI scanner, they were presented with point-light videos of their own training videos, including the original or the slightly delayed sound, and had to evaluate how well they performed on each single trial. For the undelayed conditions, we replicated A1 attenuation and enhanced pSTG and SMA engagement for tap dancing (intentionally generated sounds) vs. hurdling (incidentally generated sounds). Delayed auditory feedback did not negatively influence behavioral rating scores in general. BOLD response transiently increased and then adapted to repeated presentation of point-light videos with delayed sound in pSTG. This region also showed a significantly stronger correlation with the SMA under delayed feedback. Notably, SMA activation increased more for delayed feedback in the tap-dancing condition, covarying with higher rating scores. Findings suggest that action evaluation is more strongly based on top-down predictions from SMA when sounds of intentional action are distorted.